Development of leftover rice/gelatin interpenetrating polymer network films for food packaging - Li Sijia (De Gruyter, 2021)
Waste biomass can be used as a raw material for food packaging. Different concentrations of gelatin (GEL) were introduced into the leftover rice (LR) system to form an interpenetrating polymer network (IPN) for improving the properties of the films. The structure and morphology of films were evaluated by Fourier transform infrared, scanning electron microscopy, and atomic force microscopy, which showed good compatibility between LR and GEL. The moisture content and oil absorption rate of IPN films were down by 105% and 182%, respectively, which showed better water and oil resistance than the LR film. In addition, increasing GEL concentration led to enhancement in the tensile strength of films from 2.42 to 11.40 MPa. The water contact angle value of the IPN films (117.53°) increased by 147% than the LR film (47.56°). The low haze of IPN films was obtained with the increment of the mutual entanglement of LR and GEL. The 30–50% GEL addition improved the water vapor barrier and thermal stability properties of the IPN films. This study highlights that LR as waste biomass can have a practical application in food packaging.